A Comprehensive Bibliometric Analysis Trend of the Top 100 Most Cited Publications in Frailty Research - Sitimuawanah; Azliyana Azizan; Nova Relida Samosir; Renni Hidayati Zein; Ismaningsih; Susi Endrini (POLTEKKES KEMENKES PONTIANAK, 2024)
Frailty among older adults is a critical health issue with complex dimensions. This study presents a bibliometric analysis of frailty literature from 1990 to 2023, focusing on publication trends, leading contributors, and highly cited works.Methods: Using Web of Science and Scopus databases, the top 100 publications were analyzed to identify key countries, institutions, and research themes shaping the field. Results indicate a consistent growth in frailty-related research, with Web of Science emerging as a primary source. Leading countries and institutions demonstrate varying contributions, while highly cited papers highlight pivotal advancements. The findings underscore disparities in global research output and the role of influential journals in shaping geriatric health discourse. This analysis provides valuable insights into research gaps and serves as a guide for future studies and interventions in frailty management.